Cancer stem cells: AMLs show the way. (26th October 2005) - Bonnet, D.
Abstract : The blood-related cancer leukaemia was the first disease where human CSCs (cancer stem cells), or LSCs (leukaemic stem cells), were isolated. The haematopoietic system is one of the best tissues for investigating CSCs, since the developmental hierarchy of normal blood formation is well defined. Leukaemia can now be viewed as aberrant haematopoietic processes initiated by rare LSCs that have maintained or reacquired the capacity for indefinite proliferation through accumulated mutations and/or epigenetic changes. Yet, despite their critical importance, much remains to be learned about the developmental origin of LSCs and the mechanisms responsible for their emergence in the course of the disease. This report will review our current knowledge on LSC development and finally demonstrate how these discoveries provide a paradigm for identification of CSCs from solid tumours.